2016
DOI: 10.1055/s-0042-111684
|View full text |Cite
|
Sign up to set email alerts
|

Acute Reduction of Incretin Effect and Glucose Intolerance in Rats by Single Intragastric Administration of 3-deoxyglucosone

Abstract: Secretion of glucagon-like peptide-1 has been suggested to be impaired in T2DM and in conditions associated with hyperglycemia. 3-Deoxyglucosone, a dietary composition, has been suggested as an independent factor for the development of prediabetes. A-pathophysiological very high condition of 3DG concentrations administered i. v. induced acute glucose intolerance in rats. In this study, to examine the acute effects of single intragastric administration of 3DG at dose of potentially single-meal intake on plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 38 publications
4
11
0
Order By: Relevance
“…(24) It is also a risk factor for cardiovascular disease and metabolic syndrome. (2) Glucose intolerance caused by high-glucose load, as shown by our results, may be crucial reason that dietary glucose increases T2DM incidence, and other chronic diseases risk.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…(24) It is also a risk factor for cardiovascular disease and metabolic syndrome. (2) Glucose intolerance caused by high-glucose load, as shown by our results, may be crucial reason that dietary glucose increases T2DM incidence, and other chronic diseases risk.…”
Section: Discussionsupporting
confidence: 51%
“…(1) Dietary factors are considered to play an important role in the development of T2DM because they can influence the digestion rate, metabolism and blood glucose response. (2,3) Saturated fat intake is closely associated with insulin resistance and T2DM, which has been investigated extensively. However, the role of carbohydrate in the process is less clear.…”
mentioning
confidence: 99%
“…Studies in diabetic patients have suggested that 3DG is associated with diabetes (Niwa 1999, Kusunoki et al 2003. Our previous studies in clinical and animal research have indicated 3DG as an independent factor for the development of prediabetes (Jiang et al 2012, Liang et al 2016a, Zhang et al 2016, Wang et al 2017. Acute and two-week 3DG administration by gastric gavage induced acute glucose intolerance and glucose homeostatic dysregulation in rats, respectively.…”
Section: Introductionmentioning
confidence: 89%
“…The GLP-1 secretion in response to oral glucose was impaired in rats after 3DG administration by gastric gavage In mouse enteroendocrine cell line STC-1, treatment with 3DG induced a reduction in glucose-stimulated GLP-1 secretion (Zhang et al 2016, Wang et al 2017. Our previous studies revealed that 3DG-mediated inhibition of endogenous GLP-1 secretion was a mechanism linking 3DG with acute glucose intolerance and glucose homeostatic dysregulation in rats (Zhang et al 2016, Wang et al 2017. Therefore, it is conceivable that the STRs pathway is linked with the harmful effects of 3DG on glucose homeostasis by decreasing GLP-1 secretion.…”
Section: Introductionmentioning
confidence: 99%
“…The glucose uptake was measured by using 2-[N-(7nitrobenz-2-oxa-1,3-diazol-4-yl) amino]-2-deoxyglucose (2-NBDG) (Cayman Chemical Co., Ann Arbor, MI, USA), as previously described (Wang et al 2017). The STC-1 cells were plated in 96-well plate for 48 h and then washed with Krebs-Ringer bicarbonate (KRb) buffer (4A Biotech Co. Ltd., Beijing, China).…”
Section: Measurement Of Glucose Uptakementioning
confidence: 99%